The value of immunohistochemical methods in diagnosing endometrial carcinoma - Dundr, Pavel; Němejcová, Kristýna; Bártů, Michaela; Bennett, Rosalie Jana; Skálová, Helena; Janega, Pavol; Stružinská, Ivana (Ceskoslovenska patologie, 2021)
The goal of this manuscript is to provide an overview of the significance of immunohistochemical methods in diagnosing endometrial carcinoma. The main points discussed include: the use of immunohistochemistry in the differential diagnosis of the main histological types of endometrial carcinoma, the difference between primary serous endometrial carcinoma and the involvement with high grade serous carcinoma of another primary source, the diagnosis of undifferentiated/dedifferentiated endometrial carcinoma, and diagnosing tumours with neuroendocrine differentiation. The role of p53 expression evaluation is also emphasized as a special area of interest, not only in the context of differential diagnosis, but also from the point of view of the prognosis and prediction of endometrial carcinoma as an ancillary marker for subtypization of these tumours.
Keywords: Carcinoma, Endometrioid; Humans; diferenciální diagnóza; Biomarkers, Tumor; endometrial cancer; Female; Endometrial Neoplasms; Diagnosis, Differential; lidé; Immunohistochemistry; Endometrial carcinoma; endometrioid carcinoma; clear cell carcinoma; imunohistochemie; nádorové biomarkery; endometroidní karcinom; ženské pohlaví; immunohistochemistry; undifferentiated / dedifferentiated carcinoma; nádory endometria; serous carcinoma